2015
DOI: 10.1158/0008-5472.can-14-2397
|View full text |Cite|
|
Sign up to set email alerts
|

Ormeloxifene Suppresses Desmoplasia and Enhances Sensitivity of Gemcitabine in Pancreatic Cancer

Abstract: The management of pancreatic ductal adenocarcinoma (PDAC) is extremely poor due to lack of an efficient therapy and development of chemoresistance to the current standard therapy, gemcitabine (GEM). Recent studies implicate the intimate reciprocal interactions between epithelia and underlying stroma due to paracrine Sonic hedgehog (SHH) signaling in producing desmoplasia and chemoresistance in PDAC. Herein, we report for the first time that a nonsteroidal drug, ormeloxifene (ORM), has potent anti-cancer proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 47 publications
(71 reference statements)
1
56
0
Order By: Relevance
“…Interestingly, ORM treatment arrested PrCa cells in in G0/G1 phase of cell cycle and induced apoptosis. These results are consistent with similar previous findings in other cancer cells (12,13). It has been shown that cyclins and cyclin-dependent kinases (CDKs), play a critical role in cell cycle progression; their deregulation leads to cell cycle arrest (53).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, ORM treatment arrested PrCa cells in in G0/G1 phase of cell cycle and induced apoptosis. These results are consistent with similar previous findings in other cancer cells (12,13). It has been shown that cyclins and cyclin-dependent kinases (CDKs), play a critical role in cell cycle progression; their deregulation leads to cell cycle arrest (53).…”
Section: Discussionsupporting
confidence: 94%
“…Similar C max values for ORM also detected in breast cancer patients treated with either 30 mg, twice a week for 12 weeks (C max 54.98 ± 14.19 ng/ml) or 60 mg of ORM on alternate days for 1 month (C max 135 ± 15.5 ng/ml). These studies indicate that ORM is a non-toxic, highly bioavailable and shown potent anti-cancer effects against breast cancer (10), HNSCC (11), ovarian (12) and pancreatic cancer (13). However, molecular mechanisms of its anti-cancer properties are not well understood.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings are reminiscent of recent studies demonstrating that two independent genetic strategies to reduce myofibroblasts in the stroma of pancreatic cancers resulted in enhanced tumor aggressiveness (44,45). However, while genetic deletion of Shh resulted in enhanced tumor growth (45), pharmacologic targeting of the Hh pathway improved drug delivery and reduced tumor invasion and metastasis (46,47). These contrasting data reinforce the notion that stromal effects on tumor progression and metastasis may be highly contextual and that stromal cells can play both tumor-promoting and tumor-suppressing roles dependent on the tumor type and location.…”
Section: Discussionmentioning
confidence: 64%